Crystal structure of N-(4′-chloro-[1,1′-biphenyl]-2-yl)formamide, C13H10ClNO - Du Mo; Xu Xiaona; Tong Hongjuan (Zeitschrift für Kristallographie - New Crystal Structures)
C13H10ClNO, monoclinic, P21 (no. 4), a = 4.3011(7) Å, b = 11.2236(19) Å, c = 11.776(2) Å, β = 94.281(5)°, V = 566.90(16) Å3, Z = 2, Rgt(F) = 0.0420, wRref(F2) = 0.0827, T = 170 K.